The impact of employee engagement on performance in the South African gold mining industry - Rusere, Jeremy (University of the Witwatersrand, Johannesburg, 2022)
The purpose of the study was to evaluate factors that influence employee engagement at five gold mining companies in South Africa as well as to determine the effect of employee engagement on employee performance. Additionally, the research aimed to recommend strategies that promote employee engagement at the concerned companies. The research followed a quantitative approach, whereby data collection was by means of a questionnaire distributed online to 600 participants out of which 329 participants provided valid responses. Standard multiple linear regression was applied to the data set to determine the cause-and-effect relationships between eight predictors (compensation, work from home, work environment, organisational policies, training and career development, team and co-worker relationship, employee wellbeing and leadership) and employee engagement. Similarly, the research applied multiple regression analysis to establish the influence of employee engagement on employee performance. The research found that compensation as well as work from home were statistically significant and positively predicted employee engagement. Based on these findings, this empirical work recommended executives of the five gold mining companies to review compensation of the workforce with a view to drive employee engagement in this economically crucial industry
A research report submitted in partial fulfillment of the requirements for the degree of Master of Business Administration to the Faculty of Commerce, Law, and Management, University of the Witwatersrand, Johannesburg, 2022
Keywords: Employee engagement; Gold mining; Work environment; Mining; UCTD; SDG-8: Decent work and economic growth